2005
DOI: 10.1111/j.1399-5618.2004.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinations in bipolar disorder: characteristics and comparison to unipolar depression and schizophrenia

Abstract: This study provides detailed descriptive data regarding the frequency (cross-sectional) and characteristics of hallucinations in a large sample of patients with BPD, major depression or schizophrenia. Our results suggest a link of lower education and the presence of hallucinations in major affective disorders. The significance of this finding, as well as the role of anxiety in hallucinating patients, requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
129
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 28 publications
12
129
0
2
Order By: Relevance
“…The most frequent kinds of hallucinations were auditory in all groups of patients, including BPP patients, unlike what has been found in adults [29].…”
Section: Clinical Features and Antecedentsmentioning
confidence: 84%
“…The most frequent kinds of hallucinations were auditory in all groups of patients, including BPP patients, unlike what has been found in adults [29].…”
Section: Clinical Features and Antecedentsmentioning
confidence: 84%
“…21,29 Furthermore, psychotic symptoms have been found to occur in mood disorders, though at a lower prevalence than in schizophrenia. 5 There are several explanations, though speculative, for this finding. Hawton et al 21 have argued that these psychotic symptoms, particularly occurring in the early stages of the illness, cause the patient to feel a sense of loss of control of self and that it is this that may be the cause of the suicidal behavior, rather than a risk factor.…”
Section: Discussionmentioning
confidence: 96%
“…Approximately 50%-75% of patients with bipolar disorders concurrently experienced psychotic symptoms, 3 and these symptoms have been reported at a lifetime prevalence of 90%. 4 In a crosssectional survey of 4972 hospitalized subjects, Baethge et al 5 reported that the prevalence of psychotic symptoms such as hallucinations, delusions, and formal thought disorder and psychomotor disturbances such as catatonia ranged from 5.9% in unipolar depressed patients to 61.1% in schizophrenic patients. Schizophrenia and other psychotic disorders, such as mood disorders, which are associated with completed suicide, have been found to be comorbid in various combinations.…”
mentioning
confidence: 99%
“…However, there have been relatively few recent, systematic studies on the prevalence of hallucination and associated factors in SZ or schizoaffective disorder (SZA), especially from non-Caucasian samples. Recently, Baethge et al (2005) estimated the cross sectional prevalence of hallucinations among inpatients with schizophrenia at 61.1%. A systematic study of hallucinations among US patients with schizophrenia was reported in 1990 (Mueser et al 1990).…”
Section: Introductionmentioning
confidence: 99%